Modified Library Construction Method for 3-5kb Illumina Mate-pair Libraries - Moraga, David (Association of Biomolecular Resource Facilities, 2013)
NextGen sequencing is a powerful and cost efficient tool for ultra-high-throughput genome and transcriptome analysis. One of the key features of next generation sequencing is de novo whole genome sequencing, but assembly and genome finishing is still a major challenge due to short reads generated by these technologies. The 2kb-5kb mate pair reads combined with Illumina short pair-end reads are used in getting better genomic coverage across the genome. The standard 2kb-5kb Illumina mate-pair library construction protocol does not allow barcoding, and has built-in limitations that prevent getting more than 36bp reads at either end, as increasing read length can lead to elevated error rate. This is due to the fact that the junction reads cannot be identified easily if working with de novo assembly or those reads got discarded, since they would not align to reference sequence. Here, we demonstrate a modified 2kb-5kb mate pair library construction protocol for Illumina technologies that allows long barcoded, mate-paired reads without increasing error rates.